Dynamics of the golf club-grip interaction - Brown, C.; McPhee, J. (Proceedings, 2018)
A two degree of freedom hand-grip model was developed and simulated with a golfer downswing model, which contained an experimentally validated flexible shaft model. Experimental modal analysis was performed on a golf club to derive frequency response functions for both fixed-free and hands-free boundary conditions. Simulated frequency response functions were generated with the developed grip model to impose a hands-free boundary condition. Direct collocation using GPOPS-II was utilized to optimize the swing model with and without the grip model. An increase in clubhead velocity and decrease in shaft deflection was observed with the grip model implemented. In addition, the direct collocation approach resulted in similar joint angle trajectories, shaft deflection patterns, and joint torque profiles to those reported in the literature.